(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to examine dynamic thiol-disulfide balance, an indicator of oxidative stress, in children with stage 3-5 chronic kidney disease (CKD).Material and Methods: Native thiol (Nt), total thiol (Tt) and disulfide (DS) levels were determined spectrophotometrically in 27 children with CKD (14 non-dialysis, 13 hemodialysis) and 40 healthy controls.Results: Albumin, Nt, Tt and DS levels were markedly lower in CKD patients than in controls. However, the DS/Nt values were not statistically significant between the two groups. When Nt, Tt, DS and DS/Nt values were adjusted for albumin levels, Tt and Nt levels were lower in CKD patients than controls. In the CKD group, Nt and Tt levels were positively correlated with the albumin and estimated glomerular filtration rate and negatively with urea and creatinine. Conclusion: According to these results, decreased Nt and Tt levels in patients with CKD stages 3–5 may be evidence of exposure to oxidative stress. Keywords: Albumin; chronic kidney disease; thiol oxidation; thiol-disulfide balance.